Cultures en conflit et rite de passage dans le sommeil du juste de Mouloud Mammeri - Dalil Slahdji (Multilinguales)
Our objective in this article is to clarify some aspects of the cultural issues included in Mouloud Mammeri’s Le Sommeil du juste (1955) in order to demonstrate that interactions between the Kabyle culture and French culture during the colonization of Algeria generated conflicts between the two communities leading to an impossible rapprochement between them. For this purpose, we followed the evolution of the central character, Arezki, in a world of fiction built on the theory of the inadequacy of the values of republican humanism, advocated in the books and by the masters of the French school, with the colonial reality. We showed that this antagonism is strong enough to cause Arezki’s progressive « désocialisation ».